Have greed and rapidly rising wages triggered a profit-wage-price spiral? Firm-level evidence for Belgium - Gert Bijnens; Cédric Duprez; Jana Jonckheere (National Bank of Belgium, 2023)
Our study of Belgian firms found that 2022 price increases were largely attributable to rising intermediate input costs. Wage increases also contributed to prices hikes. Interestingly, markups appeared to play no role in driving up prices and in fact decreased or even offset the contribution of wages. In a country with automatic wage indexation, this is an important point for discussion in the debate on the profit-price or wage-price spiral.
Keywords: D22; D4; E3; J3; L11; 330; markups; greedflation; wages; profits; wage-price spiral; profit-wage-price spiral; profit-price spiral